Manajemen Program Siaran Suara Persada, Radio Persada FM Dalam Mempertahankan Eksistensi di Era Digitalisasi - Yefi Dyan Nofa Harumike; Endah Siswati; Fera Tara Batari (Universitas Islam Balitar, 2021)
Radio is one of the communication media that used to be a primadonna in society. However as media technology grew rapidly, radio became less attractive. Radio had to fight to maintain its existence in the media community. Various efforts are made by radio to reclaim the hearts of its listeners through improving the quality of broadcasting until the renewal, improvement and development of the program. Radio Persada faces the same problem. Radio Persada is a Local Public Broadcasting Institution (LPPL) in Blitar Regency that is independent, neutral, and non-commercial. It produces broadcast programs not solely to meet the demands of capitalism, liberalism, market tastes, or government mouthpiece, but primarily to carry out its function as a mass media serving the interests of the public. Persada is the flagship program of Radio Persada that seeks to realize the function of the service. Programs whose content prioritizes local information or news and live reportage is broadcast since 2018 and still exists today. This research aims to understand the management of Suara Persada program in an effort to maintain its existence in the era of digitization. Research is conducted using qualitative methods with data collection techniques through interviews, observations and documentation studies. This research found several faktors that influence the existence of Suara Persada program, namely; 1) excellence in serious but relaxing packaged local content, 2) community engagement through citizen journalism in Suara Persada program, 3) implementation of program management that follows developments in all stages of planning, organizing, influencing and controling activities, 4) the use of streaming channels and the utilization of social media (Facebook and Instagram), 5) consistency in maintaining a two-way communication system using various communication media including social media.